(untitled) (World Science, 2022)
The use of morpho-metabolic approaches has a great practical importance in evaluation of the effectiveness of antihyperglycemic therapy in clinical trials, in particular those related to new classes of inhibitors of sodiumdependent glucose-2 cotransporter inhibitors that have the ability to counteract many diabetic complications and cardiovascular disease. The aim of the study was to study the effect of treatment with SLGT2 inhibitors on morphological and metabolic parameters in men and women with type 2 diabetes. Materials and methods. During the study, 205 patients with type 2 diabetes, aged 30 to 81, with a disease duration of 1 to 20 years were examined. Patients underwent a clinical examination in the Department of Age Endocrinology and Clinical Pharmacology of the Institute of Endocrinology and Metabolism. V.P. Komissarenko of the National Academy of Medical Sciences of Ukraine. Patients received antihyperglycemic, antihypertensive and dyslipidemic therapy. Results. The study of anthropometric, morphological and biochemical parameters in groups of men and women with type 2 diabetes in the dynamics of longterm (12 month) use of iSLGT2- dapagliflozin allowed to identify certain sexual characteristics of the effects of this drug. In men group have been seen a gradual decrease in visceral fat levels during therapy. A decrease in BMI, BP, body weight and uricemia in men is most likely associated with a decrease in abdominal obesity and decreased insulin secretion. In women group use of dapagliflozin showed a significant decrease in total and visceral fat, accompanied by a decrease in relative water content, muscle and bone mass. Conclusions. Treatment of patients with type 2 diabetes with drugs of the group iSLGT2 for 12 months has reduced the degree of obesity and improved some indicators of body composition, uric acid.